Neem Leaf Extract: An Acaricide Against Adult Cattle Tick (Boophilus microplus) - Carmela G. Blando (Warmadewa University Press, 2024)
This study was conducted to evaluate the acaricidal effect of Neem Tree Leaf Extract (Azadirachta indica) using varying levels of concentrations at different lengths of exposure and to compare its efficacy with Organophosphate. The Experiment was laid out in Completely Randomized Design (CRD) with five treatments, replicated three times. The treatments evaluated were as follows: T1 – Organophosphate (Control); T2 – 25% Neem Tree Leaf Extract; T3 – 50% Neem Tree Leaf Extract; T4 – 75% Neem Tree Leaf Extract; and T5 – 100% Neem Tree Leaf Extract. Filter papers were dipped with the extracts and matted in petridishes. The ticks were placed in the treated filter papers with corresponding levels of Neem Tree Leaf Extract. There were three observations (60, 90 and 120 minutes) used to determine the effect and the killing duration of the extract. All the levels of the Neem tree leaf extract concentration used could kill ticks of cattle, however, the killing depends upon the level of concentrations and the duration of exposure. At higher concentrations, it was proven that the killing effect of the Neem tree leaf extract to adult ticks were faster than the extract at lower concentration. Based on the result of the study, the use of Organophosphate (control) was statistically similar to that of 100 percent Neem tree leaf extract in killing ticks at a maximum length of one hundred twenty minutes exposure.